2019
DOI: 10.30519/ahtr.573163
|View full text |Cite
|
Sign up to set email alerts
|

Enogastronomy in Northern Portugal: Destination Cooperation and Regional Identity

Abstract: This study aims to understand how conflicting stakeholders' interests and agendas of the public, private and non-profit sectors may affect the management of the tourism destination identity. It focuses on Northern Portugal, a geographical area with contrasting characteristics, ranging from coastal urban areas to rural hinterland, each dealing with different development issues. The study is qualitative in nature, being carried out using indepth interviews conducted with various stakeholders (public, private and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…In the case of external conditions, the most important were, as already indicated, natural and geographical conditions. Rachão et al (2019) also indicated that the specific features of the region determine the development of the enotourism offer and the formation of territorial identity. These issues, therefore, have a significant impact on the development of the wine industry because, thanks to them, it is possible to attract tourists interested in both enotourism and enogastronomy (wine and gastronomy), as well as taking advantage of other attractions offered by entrepreneurs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the case of external conditions, the most important were, as already indicated, natural and geographical conditions. Rachão et al (2019) also indicated that the specific features of the region determine the development of the enotourism offer and the formation of territorial identity. These issues, therefore, have a significant impact on the development of the wine industry because, thanks to them, it is possible to attract tourists interested in both enotourism and enogastronomy (wine and gastronomy), as well as taking advantage of other attractions offered by entrepreneurs.…”
Section: Discussionmentioning
confidence: 98%
“…Winemakers can focus on growing vines without excessive use of plant protection products (Svobodová et al, 2014) and supporting production using biostimulants (Filipczak et al, 2016). Moreover, residents must promote a given place and create its identity (Rachão et al, 2019) because it builds the region's reputation (Menival, Charters, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Estudos anteriores consideraram a gastronomia no contexto do enoturismo, como o de Rachão et al (2019) que forneceu uma visão teórica sobre a relação entre as partes envolvidas com alimentos, vinhos e turismo e como esta colaboração pode influenciar a identidade de um destino/território, também o de Gabardo e Valduga (2021) que fizeram recortes em relatos de experiências de enoturistas para analisar quais fatores contribuíram para uma viagem memorável e de alto valor agregado, assim como a pesquisa de Silva et al (2016) que analisou a relação do vinho e gastronomia do Vale dos Vinhedos como produto turístico e levou em consideração suas dinâmicas territoriais.…”
Section: Introductionunclassified
“…Due to their contributions to regional and local development, food, wine and other local products were increasingly acknowledged as central to unique, immersive and rural tourist experiences, yet the corresponding dynamics still require a better understanding [12][13][14][15][16]. With visitors becoming more interested in assuming a central role in tourism experiences, analysing how they become involved in these experiences and understanding their expectations is crucial.…”
Section: Introductionmentioning
confidence: 99%